Whole-cell microtiter plate screening assay for terminal hydroxylation of fatty acids by P450s. Issue 36 (14th April 2016) - Weissenborn, Martin J.; Notonier, Sandra; Lang, Sarah-Luise; Otte, Konrad B.; Herter, Susanne; Turner, Nicholas J.; Flitsch, Sabine L.; Hauer, Bernhard
Abstract : A whole cell screening assay for terminal hydroxylases was developed based on a readily available galactose oxidase enzyme. Abstract : A readily available galactose oxidase (GOase) variant was used to develop a whole cell screening assay. This endpoint detection system was applied in a proof-of-concept approach by screening a focussed mutant library. This led to the discovery of the thus far most active P450 Marinobacter aquaeolei mutant catalysing the terminal hydroxylation of fatty acids.